LEARNING GEOMETRY TRANSFORMATIONS USING BATIK MOTIFS: SYSTEMATIC LITERATURE REVIEW - Yanto, Yufitri; Zulkardi; Putri , Ratu Ilma Indra; Nusantara , Duano Sapta (HISTOGRAM: Jurnal Pendidikan Matematika, 2024)
This article describes the results of research on learning geometric transformations using batik motifs as teaching material for students. The research method chosen was the Systematic Literature Review (SLR) method, using the PRISMA protocol. The selection process followed the four stages of PRISMA: identification, screening, eligibility, and inclusion. The study involved documenting and reviewing seven articles related to geometric transformations using batik motifs. The findings indicate that the use of batik motifs in teaching geometric transformations can positively impact students' learning.